PRODUCTION AND MARKETING OF CATFISH HATCHERY BUSINESS (Clarias sp) IN HANGTUAH VILLAGE PERHENTIAN RAJA SUB-DISTRICT KAMPAR REGENCY RIAU PROVINCE - Sarlina, Lovita; Zulkarnaini, Zulkarnaini; Hendrik, Hendrik (Jurnal Online Mahasiswa (JOM) Bidang Perikanan dan Ilmu Kelautan, 2020)
ABSTRACTThis study was aimed to determine how much seed production and know the marketing channels and marketing areas for catfish seeds in the Hangtuah village. The research method used in this study is a survey method with 21 respondents. Based on research results, the amount of catfish seed production in Hangtuah Village Perhentian Raja Sub-District Kampar Regencyin one year size 2-3 cm can produce 171.528.205 fish seeds, size 3-4 cm can produce 132.646.154fish seeds, and size 4-6 cm can produce 26.405.128 fish seeds. Total seed production in Hangtuah Village in one year is 330.579.487 fish seeds. The marketing of catfish seeds is marketed in the area of riau province and outside the riau province. Size 2-3 cm are more widely marketed around hangtuah villages while size 3-4 cm is marketed outside of riau province such as North Sumatera, Jambi, and South Sumatera.Keywords:  Production, Marketing, Fish Seed, Hangtuah District